Properties of foam concrete with fixed percentage of expanded polystyrene - Nuh Muizzuddin, Ahmad Fauzi. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Foam concrete can be classified as a lightweight concrete which consists of cement, sand, water and foam. The use of foam concrete has been used widely across countries such as U SA, United Kingdom and Sweden. The main specialties of foam concrete are its low density, acceptable strength for structure use and high workability. These will result in reduction of dead load, faster building rates in construction and lower the handling costs. In order to improve the properties of foam concrete, many researches are done such as adding different material as fillers, superplasticizers and other admixtures. In t his project, the properties and behavior of foam concrete containing fixed perce ntage of expanded polystyrene was investigated. The properties studied were compressive strength, absorption capacity, density test and workability of foam concrete. With limitations of 20% and 30% of expanded polystyrene used, different results were obtai ned. The experimental results show that the foam concrete with higher percentage of expanded polystyrene gives lower strength and density. The results also show that increasing foam percentage provide higher workability and capacity of water absorption. Th us, percentages of foam and expanded polystyrene influence the properties of foam concrete.